2017
DOI: 10.3390/coatings7110187
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Wear Performance of Carbide Tools with TiB2 PVD Coating under Varying Machining Conditions of TiAl6V4 Aerospace Alloy

Abstract: Tribological phenomena and tool wear mechanisms during machining of hard-to-cut TiAl6V4 aerospace alloy have been investigated in detail. Since cutting tool wear is directly affected by tribological phenomena occurring between the surfaces of the workpiece and the cutting tool, the performance of the cutting tool is strongly associated with the conditions of the machining process. The present work shows the effect of different machining conditions on the tribological and wear performance of TiB 2 -coated cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…X‐ray photoelectron spectroscopy (XPS) measurements were performed at various time intervals on TiB 2 electrodes operated at j =10 mA cm −2 . The high‐resolution XP spectrum of the B 1s region (Figure ) prior to OER shows peaks at 187.6 and 192.9 eV, corresponding to TiB 2 and B 2 O 3 respectively . With increasing reaction times the peak intensity at 189.5 eV increases, which can be assigned to growing amounts of TiBO x .…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) measurements were performed at various time intervals on TiB 2 electrodes operated at j =10 mA cm −2 . The high‐resolution XP spectrum of the B 1s region (Figure ) prior to OER shows peaks at 187.6 and 192.9 eV, corresponding to TiB 2 and B 2 O 3 respectively . With increasing reaction times the peak intensity at 189.5 eV increases, which can be assigned to growing amounts of TiBO x .…”
Section: Resultsmentioning
confidence: 99%
“…Some software and platforms have support services to assist users in solving problems that arise in projects. PVD coatings mechanical properties prediction ANSYS 12.0 [7] Creation of a three-dimensional model describing flow fields and chemical reactions in Claus reactors COMSOL Multiphysics [24] Tribological performance and wear of coated cutting tools AdvantEdg 7.1 [16] Development of the model to evaluate the thermal performance of a solar tubular reactor ANSYS-CFX 14.0 [25] Computer simulation of internal stresses on the PVD coatings ANSYS [17] CFD analysis of Pd-Ag membrane reactor performance during process COMSOL Multiphysics 5.2.1 [29] Coating fracture surface study ABAQUS [77] Fluid dynamics and reaction assessment of diesel oil hydro treating reactors ANSYS-CFX 14.0 [30] Film thickness effect on mechanical properties of PVD coated tools DEFORM and ANSYS [78] Neutral gas flow simulations in an industrial PVD reactor ANSYS FLUENT 14.0 [31] Defects and material deformation study LS-DYNA [79] Prediction of velocity profiles, pressure profiles, density profiles and process gas distribution across the sputtering chamber ANSYS FLUENT [35] Estimate the thermo-mechanical properties of plasma sprayed composite coatings ANSYS-APDL (Parametric Design Language) [83] Modeling on chemical looping combustion (CLC) reactor with a finite volume based CFD method Not defined [94] After analyzing the literature it is observed that FEM is generally used to study, optimize or solve problems associated with mechanical properties, namely, adhesion, wear, stresses in the coating, the influence of the coating thickness, among others. Regarding CFD, there are studies associated with solving problems in aerodynamics, fluid flow, temperature, mass transport, heat transfer, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong importance of these characteristics, many studies have been done in the field of mathematical modeling and numerical simulation of coatings. One of the most influent characteristics in the performance of the coatings' mechanical properties is the thermal conductivity of the substrates and, for this reason, has been also deeply studied in the last decade [16]. In these works, the correct data treatment is important as well as the thermal and mechanical analysis and the interpretation of the simulation results [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during the machining of Ti, a dynamically formed thermal barrier TiC interlayer is formed at the built-up–carbide tool interface [ 28 ]. However, the predominant wear mechanism of the cutting tool is significantly altered as the cutting speed increases [ 40 ]. The intensity of built-up edge formation is lower at higher speeds (built-up is intensively worn out) [ 40 ].…”
Section: Case Studiesmentioning
confidence: 99%